Madame Bovary on Trial - LaCapra, Dominick (Cornell University Press, 1986)
In 1857, following the publication of Madame Bovary, Flaubert was charged with having committed an "outrage to public morality and religion." Dominick LaCapra, an intellectual historian with wide-ranging literary interests, here examines this remarkable trial. LaCapra draws on material from Flaubert's correspondence, the work of literary critics, and Jean-Paul Sartre's analysis of Flaubert. LaCapra maintains that Madame Bovary is at the intersection of the traditional and the modern novel, simultaneously invoking conventional expectations and subverting them.